Analisis Performa Turbin Angin Savonius Tipe U dengan Memvariasikan Jumlah Sudu Turbin - Setyawan, Iwan; Salim, Lutfi Laili; Sari, Sri Poernomo; Ridwan, Ridwan (Jurnal Penelitian Enjiniring, 2020)
Abstract Wind turbines are the main media that can be used to convert wind energy into electrical energy. The design of a good wind turbine determines the performance of a Wind Power Plant. The Savonius turbine on the vertical axis is an alternative for generating electrical energy because the development of the Savonius Turbine is directed at making economical ones, such as being able to operate at low wind speeds. This study aims to determine the performance of the Savonius turbine that has been made, the resulting generator power, and the efficiency of the generator used. The research was carried out using experimental methods by varying the number of blades 2,3 and 4. Testing was carried out directly in the coastal areas. The results were obtained from data processing are the largest turbine output power on the 2 blade turbine = 38.88 watts. The largest coefficient of power, the 2 blade turbine = 0.235. While the largest output power generated by the generator = 34.3 watts at the 4-blade turbine. The biggest generator efficiency is 12.02% on the 4 blade turbine.